Meta Analysis Effects of Completeness of Laboratory Tests and Medicine Supplies on Patient’s Satisfaction Level in Hospital - Ningtyas, Ayunda Prisilia Kusuma; Tamtomo, Didik; Prasetya, Hanung (Journal of Health Policy and Management, 2024)
Background: Satisfaction is a feeling that arises when someone gets a service, this feeling can be in the form of pleasure or disappointment. Service satisfaction at the hospital is very dependent on the patient, if the patient receives poor service then the patient tends to be dissatisfied with the service he gets, so that it can affect the quality of the hospital. This study aimed to analyze the effects of the completeness of laboratory tests and drugs availability on the patient satisfaction in hospital. Subjects and Method: This was a systematic review and meta-analysis with PICO model. Population: patients visiting the hospital. Intervention: completeness of laboratory tests and drug availability. Comparison: incomplete laboratory tests and no drugs available. Outcome: patient satisfaction. Data collection from databases Google Scholar, PubMed, Science Direct, and Spinger Link. The inclusion criteria used were full papers, cross sectional study, using English language, and published during 2012 and 2022. The keywords used are “Patient Satisfaction level” OR “Patient Satisfaction” AND “Hospital service” AND “Cross sectional”. Articles were analyzed using RevMan 5.3. Results: Meta-analysis included 14 cross-sectional studies. The completeness of the laboratory test (aOR= 2.19; 95% CI= 1.49 to 3.21; p= 0.001) and drug availability (aOR=2.41; 95% CI=1.15 to 5.03; p= 0.002) increased patient satisfaction. Conclusion: Completeness of laboratory tests and drug availability increase patient satisfaction. Keywords: completeness of laboratory tests, drug availability. Correspondence: Ayunda Prisilia Kusuma Ningtyas. Master’s Program in Public Health, Universitas Sebelas Maret.Jl Ir Sutami no 36 A, Surakarta 57126, Central Java, Indonesia. Email : ayunda.prisilia@gmail.com. Mobile: +6281328520526